Effect of Carbonization Temperature on Pore Formation and Adsorption Ability of Coconut Shell Activated Carbon with KOH Activator - anggita, sheilla rully; Prahesti, Arinda Yukashima Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
The high adsorption ability of activated carbon can be used in various applications, one of which is as an adsorbent in the water purification process. Coconut shell is one of the materials that can be used as raw material for active carbon due to its high levels of carbon, lignin, cellulose and hemicellulose, and has a large number of pores. Pore formation depends on the temperature, activator, and activation time used. This research aims to form active carbon from coconut shells by varying the carbonization temperature with KOH activator on pore formation and adsorption capacity. Making coconut shell carbon powder is obtained from the carbonization of coconut shells at a temperature variation of 500°C -700°C for 2 hours, then crushed and sieved with a 40 mesh size. The coconut shell carbon powder that has been sifted is then chemically activated by soaking the carbon powder in a 3M KOH activator solution for 24 hours. Next, the activated carbon powder is filtered and rinsed with distilled water (H2O) repeatedly until the pH approaches ±7. The activated carbon was placed in the oven at 120°C for 4 hours. Activated carbon powder was tested using BET for the pore volume and surface area of coconut shell activated carbon and its adsorption capacity for methylene blue dye was tested using a UV-Vis spectrophotometer. The research results show that in general the formation of pores resulting from SEM results increases in number and size as the carbonization temperature increases. The maximum pore volume and surface area obtained at a temperature of 700°C were 2,414 cc/g and 426,692 m2/g respectively. The most optimal adsorption capacity is 3957.15 mg/g at a carbonization temperature of 700°C.